1999
DOI: 10.1017/s0022112099006072
|View full text |Cite
|
Sign up to set email alerts
|

The flow structure in the near field of jets and its effect on cavitation inception

Abstract: Cavitation experiments performed in the near field of a 50 mm diameter (D) jet at ReD = 5 × 105, showed inception in the form of inclined ‘cylindrical’ bubbles at axial distances (x/D) less than 0.55, with indices of 2.5. On tripping the boundary layer, cavitation inception occurred at x/D ≈ 2, as distorted ‘spherical’ bubbles with inception indices of 1.7. To investigate these substantial differences, the near field of the jet was measured using PIV. Data on the primary flow, the strength distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 28 publications
5
42
0
Order By: Relevance
“…Although more recent studies have shown similar behaviour in various types of multi-hole nozzles, for example Nouri et al (2007), their formation process has been found to be relatively irregular while their interaction with the mean flow remains poorly understood. Other studies on cavitation performed in venturi-type nozzles, for example see Gopalan, Katz & Knio (1999) and Gopalan & Katz (2000), have employed laser diagnostics to provide insight into the mechanism of bubble entrapment into vortical flow structures, but the complexity of the geometry of diesel injectors makes it difficul to obtain such measurements. Furthermore, because of the difficulty in obtaining real-time measurements during the injection process, most of the reported experimental studies refer to experimental devices simulating operating conditions relevant to those of diesel engines.…”
Section: Introductionmentioning
confidence: 99%
“…Although more recent studies have shown similar behaviour in various types of multi-hole nozzles, for example Nouri et al (2007), their formation process has been found to be relatively irregular while their interaction with the mean flow remains poorly understood. Other studies on cavitation performed in venturi-type nozzles, for example see Gopalan, Katz & Knio (1999) and Gopalan & Katz (2000), have employed laser diagnostics to provide insight into the mechanism of bubble entrapment into vortical flow structures, but the complexity of the geometry of diesel injectors makes it difficul to obtain such measurements. Furthermore, because of the difficulty in obtaining real-time measurements during the injection process, most of the reported experimental studies refer to experimental devices simulating operating conditions relevant to those of diesel engines.…”
Section: Introductionmentioning
confidence: 99%
“…To make this comparison the results presented in figure 9 are replotted in figure 10 using a jet-based cavitation number, and typical ranges of incipient cavitation numbers for open jets reported in the literature are shown. The range of open jet data shown is from Ooi (1985), Pauchet et al (1992), Gopalan et al (1999) and Straka et al (2010). The jet in crossflow curve for the seeded case shows a near-linear dependence on R whereas the curves for the unseeded cases show a power-law dependence on R (for the P = 100 % curve σ ∞ = 1.65R −1 ).…”
Section: Cavitation Inceptionmentioning
confidence: 90%
“…Previous work on cavitation inception in open jets has used the rates of cavitation events from surface pressure, acceleration or acoustic measurements to quantify or define the inception process (e.g. Ooi 1985;Pauchet, Retailleau & Woillez 1992;Gopalan, Katz & Knio 1999;Straka et al 2010).…”
Section: Cavitation Inceptionmentioning
confidence: 99%
“…Two trends are found: r i increases with nozzle diameter and with air content. Other trends are conflicting (Gopalan et al 1999). An insufficient understanding of the underlying flow makes it difficult to interpret all differences.…”
Section: Incipient Cavitationmentioning
confidence: 99%